Função de resposta da cultura de meloeiro aos níveis de água e adubação nitogenada no vale do Curu, Ce - Monteiro, Rodrigo Otávio Câmara (2004)
To study the effect of water, nitrogen and the interaction between these factors on the economic yield and the production components of melon (Cucumis melo L.), a field experiment was carried out in the Experimental Farm Curu Valley, Pentecoste, Ceará, Brazil, from september to december, 2002. The statistical design was completely randomized blocks in split-plots, with four primary treatments, four secondary and four blocks. The main treatments corresponded to four water depths (W1=232,7; W2=334,7; W3=422,1; W4=567,8 mm) with four levels of nitrogen (N0=0; N1=75; N2=150; N3=300 kg.ha-1). The crop used was melon, hybrid AF-646, and the daily irrigations were controlled base on a class “A” evaporation tank, being the treatments W1, W2, W3 and W4, corresponding to 0,35 ECA, 0,70 ECA, 1,0 ECA and 1,5 ECA, respectively. The crop was installed at a 2,0 m x 0,5 m spacing, irrigated by a drip irrigation system with 3,75 L.h-1 emitters, space 0,5 m apart. The results showed that the water presented highly significant effect on the productivity of the melon, while the nitrogen was significant in the level of 6,43% and the interaction among the factors was not significant. The highest productivity estimated with the function was 25496,1 kg.ha- 1, corresponding to an application of 612,1 mm of water and and 224,4 kg.ha-1 of nitrogen. The maximum net income, R$/ha 3.353,24, was achieved with the application of 609,2 mm of water and 186,2 kg.ha-1 of nitrogen., providing an yield of 25384,3 kg.ha-1. The water use efficiency increased with the increasing levels of nitrogen up to the level of N 150 kg.ha-1, decreasing with the level of 300 kg.ha-1, for a maximum observed value of 70,4 kg.ha-1.mm-1 obtained with 232,7 mm of water deph and 150 kg.ha-1 of nitrogen. The economic water use efficiency was estimated as 41,66 kg.ha-1.mm-1, with the application of 186,2 kg.ha-1 of nitrogen.